The Psychological Impact of COVID-19 Pandemic on the population of Bahrain: Prevalence and Comparison study - Alsalman, Ali; Jahrami, Haitham; Mubarak, Hajar; Aljabal, Majed; Abdulnabi, Mahmood; Yusuf, Adel; Ishaq, Alharith; Bragazzi, Nicola (Acta Biomedica Atenei Parmensis, 2020)
Background and Aim:The pandemic of COVID-19 is a global crisis that is considered a stressful event directly and indirectly (via prophylactic measures taken) for people in any society. It can have an impact on mental health resulting in a plethora of symptoms.Method:This study measures the psychological impact, demonstrated by the symptoms of depression, anxiety, and stress. An online semi-structured questionnaire has been used with all participants, and with the measure The Arabic version of The Depression Anxiety and Stress Scale -21 (DASS-21). The study design was cross-sectional. Which was conducted in April-May 2020. The sample was (n=1115) from Bahrain’s population, (1081 Bahraini) and (33 non-Bahraini), aged 18 and above, 701 females, most of them were graduated and employed.Results showed 30% were with depressive symptoms, 18.2% have exhibited symptoms, and 30.8% reported stress symptoms. Females were higher than males in depressive and anxiety symptoms. While no gender differences in stress symptoms. The younger age group showed more distress across the board with symptoms reported decreasing with age. Students were also noticed to be the group reporting the highest symptoms, together with people with the lowest income.ConclusionThe study has demonstrated a high psychological impact on the population of Bahrain with around a third of the population demonstrating some level of distress.